2001
DOI: 10.1212/wnl.56.1.133
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of one-session biofeedback training in pediatric headache

Abstract: Relaxation training and thermal biofeedback are promising treatments for pediatric headache. [1][2][3][4][5] This study evaluated the effectiveness of an hour-long, biofeedback-assisted relaxation training (BART) session within the context of a multidisciplinary pediatric headache center. The objectives were to determine whether peripheral body temperature (PBT) changes obtained during the training session (T1) could be maintained when measured at the child's subsequent follow-up clinic visit (T2), and to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Treatment.— Interventions should not be merely the application of an approach used with adults to pediatrics. Treatments should be designed for and piloted with pediatric samples 14,15,22,23 . Adjustments for developmental and environmental differences from adults should be explicitly stated (eg, inclusion of parents, peers, or school personnel in treatment approaches; changes in the techniques implemented to make behavioral approaches developmentally appropriate for a young child or adolescent 24 ).…”
mentioning
confidence: 99%
“…Treatment.— Interventions should not be merely the application of an approach used with adults to pediatrics. Treatments should be designed for and piloted with pediatric samples 14,15,22,23 . Adjustments for developmental and environmental differences from adults should be explicitly stated (eg, inclusion of parents, peers, or school personnel in treatment approaches; changes in the techniques implemented to make behavioral approaches developmentally appropriate for a young child or adolescent 24 ).…”
mentioning
confidence: 99%
“…Headache severity decreased from a mean of 5.0 (0 to 10 scale; 10 = most pain) to 4.5. Average headache frequency decreased from 12.9 to 9.7 days/month, and duration also decreased from 6.9 to 5.2 h. In general, 85 % of parents reported that their child was functioning ''better'' at the end of the study [54].…”
Section: Behavioral Measuresmentioning
confidence: 87%
“…The response rate was 58 % overall; 48 % for chronic headaches and 73 % for episodic headaches [53]. Powers et al [54] looked at 20 children (mean age 11.6 years) consecutively referred for biofeedback and relaxation therapy who received standard multidisciplinary treatment and biofeedback based on headache presentation and developmental status. Children were taught age-appropriate skills in deep breathing, progressive muscle relaxation, and guided imagery.…”
Section: Behavioral Measuresmentioning
confidence: 99%
“…Because anxiety and pain are associated with increased sympathetic activity and arousal, the use of relaxation techniques that induce parasympathetic activity and subsequent reduction in sympathetic activity represents a logical choice for intervention. Indeed, empirical evidence exists supporting the use of such treatment, reporting treatment gains in physiological parameters and control of client-presented problems (Holden et al, 1999;Powers, 1999;Powers et al, 2001). Within the treatment session, patients are taught relaxation through the use of one of a variety of scripts or manuals, many of which are designed especially for use with children.…”
Section: Overview Of Behavioral and Cognitive-behavioral Therapiesmentioning
confidence: 99%